Patient Perception of Nurse Caring in Faisal Islamic Hospital Inpatient Room Makassar - Hardiyanti, Sitti; Ramli, Rachmad; Rahmat, Rezqiqah Aulia; Rosida, Rosida; Ervan, Ervan; Aripa, Lusyana (International Journal of Health Sciences, 2023)
Caring is holistic nursing that is useful to support the client's recovery process and how to establish a caring relationship with the client and take responsibility for the client's condition. The caring relationship carried out by nurses is a unique nursing process in service. According to Leininger in expressing caring behavior is comfort, affection, care, coping behavior, empathy, support and trust. The purpose is to know the assertive attitude of nurses in providing nursing services at the Inpatient Installation of Faisal Islamic Hospital Makassar and to know the verbal and non-verbal communication of nurses in providing nursing services at the Inpatient Installation of Faisal Islamic Hospital Makassar. This type of research is descriptive research, which is a research method carried out with the main objective of making a description of the level of education, work experience, and gender towards the assertive attitude of nurses. This study was conducted in the inpatient room of Faisal Islamic Hospital Makassar, which became the population in this study were all nurses in the Inpatient Installation of Faisal Islamic Hospital Makassar, totaling 121 people with a sample that will be studied at the Inpatient Installation of Faisal Islamic Hospital Makassar as many as 55 people.